2021
DOI: 10.1186/s12884-021-03581-3
|View full text |Cite
|
Sign up to set email alerts
|

“Mine did not breastfeed”, mothers’ experiences in breastfeeding children aged 0 to 24 months with oral clefts in Uganda

Abstract: Background Appropriate breastfeeding is vital for infant and young child nutrition. Annually, oral clefts affect 0.73 per 1000 children in Uganda. Despite this low incidence, children with a cleft face breastfeeding difficulty which affect their nutrition status. In addition, knowledge on maternal experiences with breastfeeding and support is limited. We explored maternal perceptions, experiences with breastfeeding and support received for their children 0 to 24 months with a cleft attending Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…A recent study performed in Uganda showed a mean breastfeeding duration of 4.3 weeks in CLP infants and not one of the CP infants was breastfed. Data from focus group discussions and in-depth interviews revealed multiple reasons for breastfeeding failure in this group, including struggles with the breastfeeding process, difficulties in expressing breast milk, poor breast milk supply, babies choking on milk, milk spillages, and nasal regurgitation [15]. In addition, the prevalence of malnutrition in CP and CLP infants, reported by Tungotyo et al in Uganda, was 68% with 57% having moderate-to-severe malnutrition.…”
Section: Discussionmentioning
confidence: 71%
“…A recent study performed in Uganda showed a mean breastfeeding duration of 4.3 weeks in CLP infants and not one of the CP infants was breastfed. Data from focus group discussions and in-depth interviews revealed multiple reasons for breastfeeding failure in this group, including struggles with the breastfeeding process, difficulties in expressing breast milk, poor breast milk supply, babies choking on milk, milk spillages, and nasal regurgitation [15]. In addition, the prevalence of malnutrition in CP and CLP infants, reported by Tungotyo et al in Uganda, was 68% with 57% having moderate-to-severe malnutrition.…”
Section: Discussionmentioning
confidence: 71%
“…Fathers also had a high level of stigma perception. However, previous studies [ 14 , 18 ] suggested that mothers of children with CL/P experienced severe stigma or discrimination while ignoring the possibility that fathers also experienced high levels of discrimination. Two other studies [ 19 , 20 ] pointed out that the main sources of stress among fathers were the treatment process, feeding, and social stigma.…”
Section: Discussionmentioning
confidence: 99%
“…These authors revealed that the knowledge of mothers on breastfeeding and weaning-related factors was significantly associated with the monthly family income. It is worth noting that the feeding of these children should be carefully and frequently monitored to provide essential nutrients for proper growth, maintenance of general health, and Other studies have also shown breastfeeding practices below ideal rates owing to difficulties, which reveals that guidance and psychosocial support play an important role in the breastfeeding of newborns with orofacial clefts (Kaye et al, 2019;Madhoun et al, 2020;Nabatanzi et al, 2021). Murthy et al (2020) compared through a randomized control trial the efficacy of guidance using an audiovisual modulus with a traditional instructional modulus for improving the habits of assisted breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…The particular problems of newborns with cleft lip and/or palate (CL/P), regarding breastfeeding are insufficient suction, excessive air ingestion, fatigue, inadequate milk ingestion, nasal regurgitation, and excessive time to feed. The lack of satisfactory feeding may cause anxiety and stress between the mother and the baby (Silva et al, 2018;Nabatanzi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%